Wearable Wireless Tyrosinase Bandage and Microneedle Sensors: Toward Melanoma Screening. Issue 7 (18th January 2018) - Ciui, Bianca; Martin, Aida; Mishra, Rupesh K.; Brunetti, Barbara; Nakagawa, Tatsuo; Dawkins, Thomas J.; Lyu, Mengjia; Cristea, Cecilia; Sandulescu, Robert; Wang, Joseph
Abstract: Wearable bendable bandage‐based sensor and a minimally invasive microneedle biosensor are described toward rapid screening of skin melanoma. These wearable electrochemical sensors are capable of detecting the presence of the tyrosinase (TYR) enzyme cancer biomarker in the presence of its catechol substrate, immobilized on the transducer surface. In the presence of the surface TYR biomarker, the immobilized catechol is rapidly converted to benzoquinone that is detected amperometrically, with a current signal proportional to the TYR level. The flexible epidermal bandage sensor relies on printing stress‐enduring inks which display good resiliency against mechanical deformations, whereas the hollow microneedle device is filled with catechol‐coated carbon paste for assessing tissue TYR levels. The bandage sensor can thus be used directly on the skin whereas microneedle device can reach melanoma tissues under the skin. Both wearable sensors are interfaced to an ultralight flexible electronic board, which transmits data wirelessly to a mobile device. The analytical performance of the resulting bandage and microneedle sensing systems are evaluated using TYR‐containing agarose phantom gel and porcine skin. The new integrated conformal portable sensing platforms hold considerable promise for decentralized melanoma screening, and can be extended to the screening of other key biomarkers in skin moles. Abstract : Illustration of the tyrosinase wearable bandage sensor toward skin cancer screening.